THEORETICAL ANALYSIS OF THE WORKING PARTS OF A NEW DESIGN FOR SEPARATING COTTON FROM WASTE (Web of Technology: Multidimensional Research Journal, 2025)
This article investigates the issue of raw cotton being lost into waste streams during the cotton cleaning process, which remains one of the most pressing challenges in primary cotton processing enterprises today. A new grate design for a regenerator device is proposed, and the motion of cotton particles on the grate is first examined theoretically.